Ministry Policy Related To Subjects Indonesian Language and Literature in School - Fadilla, Annisa Rizky; Wulandari, Putri Ayu (Journal of Learning Improvement and Lesson Study, 2023)
This study aims to determine the development of curriculum and government policies, especially in the field of Indonesian from year to year. This study uses the literature review method to review the history of the development of educational policies in accordance with the laws in force in Indonesia, the authors also convey the problems that exist in it for the formation of a law related to the curriculum as well as the problems faced by the general public about the ministry of manpower which includes Indonesian as the main language. The results obtained from this paper are that each government regulation has its own constraints and difficulties, such as the abolition of the UKBI test for foreign workers which reduces local human resources to easily find jobs in their own regions. Likewise with curriculum changes with the constraints of remote areas lacking training while the curriculum is always developing every year following government policies in carrying out the curriculum.